1990
DOI: 10.1212/wnl.40.10.1546
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis sibling pairs

Abstract: We evaluated 48 relapsing-remitting multiple sclerosis (R/R MS) sibling pairs derived from 44 families for age and date of onset of MS symptoms, clinical course, and family history of MS. Age- and sex-matched R/R MS clinic patients provided a statistical comparison group. The age of onset tended to cluster within multiplex families. The initial symptom of MS occurred within 5 years of age in 30/48 sibling pairs compared with 16/48 controls. A positive family history of MS (other than siblings) was present in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…Overall, the risk is highest in monozygotic twins with a concordance rate of about 30% in digyzotic twins and in other siblings less than 10%, providing strong evidence for genetic factors in MS. [127][128][129][130] In siblings, the earliest symptoms of the disease tend to cluster by age rather than by year, suggesting that genetic factors influence the onset of the disease. [131][132][133] Based on association studies using the case-control design testing specific candidate genes and studying sporadic and familial cases, the only consistently replicated finding has been an association with the HLA-DR2 allele within the major histocompatibility complex (MHC) on chromosome 6. Data from the 1998 study by Haines et al 133 strongly indicate that sporadic and familial MS share a common genetic susceptibility.…”
Section: Clinical Presentation Of Optic Neuritismentioning
confidence: 99%
“…Overall, the risk is highest in monozygotic twins with a concordance rate of about 30% in digyzotic twins and in other siblings less than 10%, providing strong evidence for genetic factors in MS. [127][128][129][130] In siblings, the earliest symptoms of the disease tend to cluster by age rather than by year, suggesting that genetic factors influence the onset of the disease. [131][132][133] Based on association studies using the case-control design testing specific candidate genes and studying sporadic and familial cases, the only consistently replicated finding has been an association with the HLA-DR2 allele within the major histocompatibility complex (MHC) on chromosome 6. Data from the 1998 study by Haines et al 133 strongly indicate that sporadic and familial MS share a common genetic susceptibility.…”
Section: Clinical Presentation Of Optic Neuritismentioning
confidence: 99%
“…Many clinical, epidemiological, and pathological features of MS suggest that it is an infectious disease. These include the clinical course of a progressive and relapsing disease [16,17], twin studies indicating that the concordance of MS monozygotic twins is only approximately 35% and this is insufficient to implicate a purely genetic basis [18][19][20][21][22][23][24], the epidemiological occurrence of disease in clusters [25][26][27], a variability in prevalence by geographic location [28,29], an age-related acquisition risk [29], and inflammatory patterns of neuropathology [30,31] with tissue macrophages, perivascular lymphocytic infiltration, complement deposition, and increases in pro-inflammatory cytokines including TNFalpha, IL-1, IL-2, etc. [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported clustering for age at onset in affected siblings 8,[21][22][23] or in families with more complex pedigrees. 11,24 Others have not reproduced this finding.…”
Section: All Familiesmentioning
confidence: 98%